Pengaruh Pendekatan Ethno-RME Terhadap Kemampuan Pemecahan Masalah Peserta Didik - Annisa, Salsa Fitri; Zulfah, Zulfah; Rizky, Lussy Midani (Universitas Pekalongan, 2024)
This research aims to see the influence of the Ethno-RME approach on mathematical problem solving skill as seen in the results of tests on mathematical problem solving skill of class VIII students at SMP Negeri 2 Bangkinang Kota. The research was conducted to determine the differences in the mathematical problem solving abilities of class VIII students at SMP Negeri 2 Bangkinang Kota who applied the Ethno-RME approach and the mathematical problem solving skill of students who applied conventional learning. This type of research is experimental research, with a Simple Random Sampling sampling technique. The population in this study were students in class VIII of SMP Negeri 2 Bangkinang City for the 2022/2023 academic year. The research subjects consisted of class VIIIA, totaling 22 people and VIIIB, totaling 22 people. The data analysis technique used is the Independent Sample T-Test and the N-Gain test with the help of SPSS 29. Based on the N-Gain Score Test for the experimental class with the Ethno-RME approach, it is 61%, including in the quite effective category, it can be concluded that the use of the approach Ethno-RME is quite effective in improving students' mathematical problem solving skill.